Empowering Peatland Farmers: Exploring the Role of Farmer Participation in Enhancing the Quality of Honey Pineapple Commodities - Kinanti Ajenk Sari; Maswadi Maswadi; Shenny Oktoriana (Universitas Muhammadiyah Malang, 2023)
The participation of farmers in agricultural development has been identified as a crucial component for the transfer of knowledge and technology. Access to information on innovative agricultural practices is essential for farmers to implement procedures that support farming. Although active participation can take various forms, physical involvement is not the sole determinant of successful participation. Peatland honey pineapple cultivation has been a long-standing practice, and its production has experienced fluctuations over the years. The decline in honey pineapple production from 2017 onwards poses a challenge for both farmers and the district government, given the crop's potential for development in Galang Village, Mempawah Regency. This research study utilized a sample of 73 individuals and collected data through interviews, observations, and available references. Both quantitative and qualitative analyses were conducted to examine the level of farmers' participation in the development of honey pineapple commodities across three stages: participation, implementation, and evaluation. The study revealed that farmers' participation in the development of honey pineapple commodities at the participation stage fell into the independent category (1.43 >1.96), while at the implementation and evaluation stages, it entered the independent category, with values of 5.29 (>1.96) and 2.96 (>1.96), respectively. Age, education level, and length of farming experience were identified as factors that influenced farmers' participation in the development of honey pineapple commodities.